SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMA KARTU KELUARGA SEJAHTERA DENGAN PENDEKATAN TOPSIS (Studi Kasus: Desa Sri Menanti Way Kanan) - Reni Nursyanti , Rola Hengki (LPPM UNIBI, 2018)
Kartu Keluarga Sejahtera (KKS) is a card issued by the Government as a marker of poor families as a substitute for Kartu Keluarga Sejahtera (KPS) which aims to overcome poverty by providing assistance in the form of money (TNP2K, 2014). One of the villages that received assistance from KKS is Simenanti Village. Sri Menanti Village located in Batin State District Way Kanan Regency is a village that stood since 1877, the majority village is Lampung society is a village with a population of 307 families with a population of 1255 people. head of household with a population of 1255 inhabitants. The family selection system that received the KKS in the village is still not appropriate or not in accordance with the criteria of poor rice recipients. Based on interviews with Sri Menanti Village Chief, the techniques used in the selection of KKS recipients are by means or random selection system without using guidelines with predetermined criteria and without any standards. From this point of view, the selection or selection of KKS recipients in the village of Sri Menanti is still inaccurate which would harm the target households (poor households and very poor households). To solve the problem, the authors undertake the design of decision support system aimed at in order to facilitate decision making by the committee of KKS Desa Sri Menanti in the selection of recipients of KKS with predetermined criteria. The method applied in this decision support system application is TOPSIS method. The TOPSIS Method is one of the decision-making methods that uses the principle that the chosen alternative must have the closest distance from the ideal ideal solution and furthest from the ideal negative solution. So the alternative that has the shortest distance with the ideal ideal solution is the best alternative. (Juliayanti, Irawan, & Mukhlash, 2011, pp. M-66). Keywords: Kartu Keluarga Sejahtera, Decision Support System, Topsis